Screening of rice genotypes for tolerance to soil acidity and related nutritional constraints - Saha, PB; Jha, AK; Kumar, S; Prasad, K (ORYZA-An International Journal of Rice, 2022)
A field experiment was conducted in the experimental farm of Zonal Agricultural Research Station, Dumka, Birsa Agricultural University, Ranchi, JharkhandÂ during kharif 2018 to evaluate location specific genotypes for tolerance to soil acidity and related nutrient constraints in rainfed medium low lands. The experimental findings have been interpreted in terms of grain yield, crop response (%) to lime, lime use efficiency (LUE), P and K-uptake by the crop. The experiment was laid out in split plot design in which fertilizer levels (two) [NPK (RD) i.e., @ (100:50:25) kg/ha and NPK (RD) + lime @3q/ha] were taken as main plots and rice genotypes (fourteen) as sub-plots. It was found that the grain yield and nutrient uptakes (P & K) by the crop were significantly influenced by lime (irrespective of vars.) and genotype differences (irrespective of lime levels). Significantly higher grain yield (55.20 q/ha), P-uptake (17.21kg/ha) and K-uptake (19.13kg/ha) were recorded with (NPK + Lime) (irrespective of vars.). The highest crop response to lime (26.9%) and lime use efficiency (4.74 kg grain /kg lime) were recorded with JKRH3333 and BINADHAN-75, respectively, whereas the maximum increase in P-uptake (19.1%) and K-uptake (33.0%) were obtained with BINADHAN-8 and PUP-223, respectively.